AN ESSAY ON THE APPLICABILITY OF THE LINDER HYPOTHESIS IN DETERMINING THE PATTERNS OF THE ROMANIAN INTERNATIONAL TRADE - Viciu, Tania Georgia; Mihoreanu, Larisa; Costea, Carmen (Journal of Economic Development, Environment and People, 2016)
The paper tries to shed light on the effectiveness of a previously proposed and wide accepted trade model and its consistency in developing economies such as Romania. The structure and evolution of the exports and imports of Romania in the last years have indicated an increase in the intra-industry trade, and concurrently, a shift towards the commerce in predominantly capital-intensive commodities. While the Linder theorem provides useful insight into the patters of international trade formation, the hypothesis that trade is proportionate with the demand and market similarities expressed by GDP per capita, does not test out for the data available for Romania and its main economic and commercial partners. The political and economic restrictions and opportunities generated by foreign relations in the region can be attributed with the role of trade-creating forces, rather than income similarities on the markets.